Penerapan metode muraja'ah dalam upaya meningkatkan hafalan Al-Qur'an siswa Mis Khairurahmah Merbau rintis desa pantai gading kecamatan Secanggang tahun ajaran 2024-2025 - Muhammad Alwan; Kholis Thohir; Yuni Asri Ningratri (Fiqhuna: Jurnal Pendidikan Agama Islam, 2025)
The background of this study is the fact that some students still experience dif iculties in maintaining the quality of their Qur’an memorization, so an ef ective learning method is needed, one of which is the muraja’ah method. The purpose of this study is to describe how the muraja’ah method is implemented by teachers to improve students’ Qur’an memorization, as well as to identify the results and challenges faced during the learning process.This study used a qualitative descriptive approach. The rsearch subjects consisted of 1 teacher and 32 students. The data collection techniques were interviews, observations, and documentation. The results showed that the implementation of the muraja’ah method was able to improve students’ Qur’an memorization. This can be seen from the increase in the number of students who were able to memorize fluently and accurately after practicing muraja’ah regularly. Out of 32 students, 27 students succeeded in maintaining their memorization well, while 5 students still faced obstacles such as lack of discipline and insuf icient learning support from their environment. In conclusion, the muraja’ah method is proven to be ef ective in helping students maintain and improve their Qur’an memorization, although it still requires supporting strategies such as motivation.